Latest Innovations in Midwifery Practice to Raise Family Planning and Reproductive Health Awareness - Meyana Marbun; Nikmatul Khasanah; Irwandi Irwandi; Novida Ariani; Ida Widiawati (Universitas Aisyah Pringsewu, 2023)
Awareness of family planning and reproductive health is essential to Indonesian society. This is because the maternal and infant mortality rates are still relatively high, especially in rural areas. This research then aims to look at innovations that can be carried out in midwifery practice to help increase awareness of family planning and reproductive health. This research will be carried out using a descriptive qualitative approach. This research method is a literature study. This research found that family-focused health education can help reduce unwanted pregnancy, domestic violence, and maternal and child mortality rates. In addition, the presence of psychological support can also help couples deal with stress and anxiety during pregnancy and childbirth. This psychological support can ultimately help the family mentally and physically. Finally, a collaboration that occurs between governments can help people who live in areas that are marginalized or difficult to reach. Through the implementation of these innovations, it is hoped that awareness of family planning and reproductive health can increase.